Second-Order Sliding Mode Control Design Subject to an Asymmetric Output Constraint - Liu, Lu; Ding, Shihong; Yu, Xinghuo (IEEE transactions on circuits and systems. II, Express briefs, 2021)
In this brief, a novel second-order sliding mode (SOSM) control method is developed to solve the asymmetric output constraint problem by using a power integrator and barrier Lyapunov function (BLF). The new BLF is first constructed based on the asymmetric constraint condition. A novel SOSM algorithm is then constructed for the nonlinear systems with an asymmetric output constraint. Under the proposed SOSM algorithm, the output of the resulting closed-loop system will never escape from the asymmetric constraint. Finally, a pendulum system is adopted to verify the validity of the theoretical results.